Triphenylphosphonium-modified mitochondria-targeted paclitaxel nanocrystals for overcoming multidrug resistance - Xue Han; Ruijuan Su; Xiuqing Huang; Yingli Wang; Xiao Kuang; Shuang Zhou; Hongzhuo Liu (Asian Journal of Pharmaceutical Sciences, 2019)
Mitochondria are currently known as novel targets for treating cancer, especially for tumors displaying multidrug resistance (MDR). This present study aimed to develop a mitochondria-targeted delivery system by using triphenylphosphonium cation (TPP+)-conjugated Brij 98 as the functional stabilizer to modify paclitaxel (PTX) nanocrystals (NCs) against drug-resistant cancer cells. Evaluations were performed on 2D monolayer and 3D multicellular spheroids (MCs) of MCF-7 cells and MCF-7/ADR cells. In comparison with free PTX and the non-targeted PTX NCs, the targeted PTX NCs showed the strongest cytotoxicity against both 2D MCF-7 and MCF-7/ADR cells, which was correlated with decreased mitochondrial membrane potential. The targeted PTX NCs exhibited deeper penetration on MCF-7 MCs and more significant growth inhibition on both MCF-7 and MCF-7/ADR MCs. The proposed strategy indicated that the TPP+-modified NCs represent a potentially viable approach for targeted chemotherapeutic molecules to mitochondria. This strategy might provide promising therapeutic outcomes to overcome MDR. Keywords: Paclitaxel, Nanocrystals, Brij 98, Triphenylphosphonium, Multidrug resistance, Mitochondria